Group classification of systems of nonlinear reaction-diffusion equations with triangular diffusion matrix - Nikitin, A.G. (Український математичний журнал, 2007)
Group classification of systems of two coupled nonlinear reaction-diffusion equations with a general
diffusion matrix started in previous author’s works completed in present paper where all nonequivalent
equations with triangular diffusion matrix are classified. In addition, symmetries of diffusion systems
with nilpotent diffusion matrix and additional first order derivative terms are described. Завершено групову класифікацію систем двох зачеплених рівнянь реакції-дифузії з загальною матрицею дифузії, розпочату в попередніх роботах автора. A саме, прокласифіковано всі нееквівалентні рівняння з трикутною матрицею дифузії. Крім цього, описано симетрії дифузійних систем з нільпотентною матрицею дифузії та додатковими членами з похідними першого порядку.